Daily life in a Plains Indian village, 1868 - Terry, Michael Bad Hand. (New York : Clarion Books, 1999)
Depicts the historical background, social organization, and daily life of a Plains Indian village in 1868, presenting interiors, landscapes, clothing, and everyday objects.
Includes index.
Wilson's Children.
Wilson's Junior High School.
School Library Journal.
7.9
Keywords: Indians of North America -- Great Plains -- History -- Juvenile literature; Indians of North America -- Material culture -- Great Plains -- Juvenile literature; Indians of North America -- Great Plains -- Social life and customs -- Juvenile literature; Indians of North America -- Great Plains; Native Americans -- Great Plains -- History; Native Americans -- Social life and customs -- Great Plains; Native Americans -- Great Plains; Indians of North America -- Great Plains